Kumal Children Schooling: History, Culture and Parents’ Perception - Khatri, Hikamat Bahadur (Orchid Academia Siraha, 2022)
This paper aims to analyse how history, culture and parents’ perception influenced childrens’ schooling. In the context of Nepal, cultural values and norms are deeply rooted in society. So this study explores how involving children in cultural activities hampers their schooling. The study is based on field data and I organised this study into three key themes, history and tradition of Kumal people, cultural influence in Kumal children schooling and Kumal parents’ perception towards children schooling.